The Forms of Politeness Applied by English Students in Communication to Their Thesis Advisor Lecturers Via WhatsApp - Widya Wardah Maharani; Arasuli Arasuli; Ildi Kurniawan (Journal of English Education and Teaching, 2022)
This research aims to determine the forms, scales, and factors of students' politeness in communication to their thesis advisor lecturers via WhatsApp. The research design was descriptive qualitative research. The subject of this research was 54 of 2017 English students' text messages to their thesis advisor lecturers who were selected from classes A, B, and C by using the purposive sampling technique. The data were analyzed based on theory forms of politeness by Kushartanti, scales of politeness by Leech, and factors affecting politeness by Brown & Levinson's theories. From the findings of this study, there are four forms of politeness used by students, namely pronominal sentences, indirect sentences, opening sentences, and word appreciation sentences. The most widely used forms of politeness are opening sentences and appreciation words. Five politeness scales were also found, namely the cost and benefit scale, the optionality scale, the indirectness scale, the authority scale, and the last is social distance scale, where this scale is the most widely used. All politeness data are influenced by relative power and social distance, and there is no size of imposition politeness factor found. There are also two forms of impoliteness in this study, directness and without using the word appreciation and some students are classified as impolite based on the optionality scale. Students use all existing forms of politeness because they use Indonesian politeness forms and Indonesian culture, which considers these forms a sign that sentences in a conversation are considered polite. The form of politeness used by students is influenced by the politeness scale, that is social distance and vice versa. Based on the result, it can be concluded that most of the students have used politeness form when communicating with their lecturers through WhatsApp text messages.